Design and in vitro evaluation of haloperidol lactate transdermal patches containing ethyl cellulose-povidone as film formers - Sadashivaiah, R; Dinesh, B M; Patil, Uma A; Raghu, K S (Asian Journal of Pharmaceutics (AJP), 2014)
Matrix-type transdermal drug delivery systems of haloperidol lactate were prepared using different ratios of ethyl cellulose (EC):polyvinyl pyrrolidone (PVP) (3:2, 2:3, 4:1, 1:2, 2:1, and 1:4) by solvent-evaporation technique. Physicochemical parameters were characterized, and dissolution studies of the formulated films were performed. In addition, solubility studies at various values of pH were carried out, and partition coefficient in octanol/water system, flux, and enhancement ratio were also evaluated. In vitro permeation studies were done using modified Franz diffusion cells through human cadaver skin utilizing 20% PEG 400 in normal saline. Permeation studies illustrated that 4% hyaluronidase enzyme was a good enhancer. The prepared films were subjected to scanning electron microscopy (SEM) and fourier transform infrared spectroscopy (FT-IR) spectral analysis. Higuchi and Peppas models were used for optimizing the formulation.